PERFORMANCE OF RED CHILI PEPPER IN NORTH SUMATERA CASE: BERINGIN DISTRIC, DELI SERDANG REGENCY - Nasution, Amelira Haris (Universitas Djuanda, 2019)
Red chili pepper is an important commodity for the people of Indonesia. Therefore the government has set red chili pepper as a strategic commodity with a production target of 2.29 million tons in 2019. One of the centers of red chili pepper production is North Sumatera. As a production center, the problem is usually about the low prices at the farm level. This is due to the lack of a marketing channel role analysis that could accommodate farmers' aspirations, causing farmers to not have bargaining power, so farmers are only a